ระบบวิธีคำนวณพื้นที่-เวลา-ความยาวรอยเลื่อน ตามแนวระบบรอยเลื่อนตามแนวระดับ ชายแดนประเทศไทย-พม่า - ภูริณัฐ พิพัฒนเจริญกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2014)
In this study, the prospective areas of the upcoming moderate-to-large earthquake were evaluated along the Strike-slip Fault System, Thailand-Myanmar Border. In order to investigate the precursory seismic quiescence of earthquake, a statistical method, called the Region-Time-Length (RTL) algorithm were used in this study. The main dataset are the completeness earthquake catalogue occupied by 3 data sources, i.e., i) Incorporated Research Institutions for Seismology (IRIS), ii) The Global Centroid Moment Tensor (CMT) and iii) Thai Meteorological Department (TMD). After improving the earthquake catalogue, i.e., homogenizing the earthquake magnitude, earthquake declustering of foreshock and aftershock, including eliminating the man-made seismicity, 1,706 events with MW>4.8 reported during 1964-2015 were defined as the completeness data meaningful for any seismicity investigation. Then, 14 available events of the MW>4.8 earthquakes were considered for the retrospective test. After the retrospective test, it is found that r0 = 170 km and t0 = 3.5 years are appropriate characteristic parameter for the Strike-slip Fault System. As a result, this study gives me a Seismic quiescence map of study area. It shows that there are 2 prospective areas might be risk for the upcoming moderate-large earthquakes are the Northern part and Southern part of the Strike-slip Fault System, Thailand-Myanmar Border.